Management of Indonesian Listening Comprehension Skills Based on The Storytelling Method - Deka Syahbari; Deti Rostini (CV. Media Digital Publikasi Indonesia, 2026)
This research aims to describe and analyze the management of Indonesian Language listening comprehension skills in lower-grade students through the application of the storytelling method at SDN Tegal Alur 04 Pagi (Morning) and SDN Jembatan Besi 02 Petang (Afternoon), West Jakarta. The study was conducted using a qualitative approach with a case study design, involving teachers, students, and the school principal as subjects. Data was collected through observation, interviews, and document analysis. The findings indicate that both schools have implemented the functions of learning management—covering planning, implementation, direction, and evaluation—but with different styles of application. SDN Tegal Alur 04 Pagi tends to be more systematic and organized, while SDN Jembatan Besi 02 Petang is more flexible, adjusting to the learning situation in the afternoon. The storytelling method proved to have a positive impact on improving students' listening skills, although the strategy of implementation differed according to the conditions of each school.